4th Film Festivals Symposium: In Pursuit of the Audiences of Film Festivals - Sivas, Sena Öndün (Semire Ruken ÖZTÜRK, 2025)
Bu yazı, 27–28 Mayıs 2025 tarihlerinde 22. Eskişehir Uluslararası Film Festivali kapsamında düzenlenen “4. Film Festivalleri Sempozyumu”nun eleştirel bir değerlendirmesini ayrılmıştır. “Film festivali seyircisi” teması etrafında şekillenen sempozyum, film festivallerinin değişen dinamiklerini tartışmak üzere akademisyenleri, sektör profesyonellerini ve öğrencileri bir araya getirmiştir. İki gün süren programda yirmi dört bildiri sunumu, iki davetli konuşmacı, iki panel oturumu ve bir yuvarlak masa tartışması yer almıştır. Sunumlar; film festivalleri ve sektör dinamikleri, değişen seyirci profilleri, dijitalleşme, ulusal ve tematik festivaller, temsil, sektörel dönüşümler, festivallerin ulusal ve bireysel bellek üzerindeki rolü ile seyirciye yönelik eğitim odaklı yaklaşımlar ve programlama stratejilerindeki değişimler gibi konuları ele almış ve film festivallerinin değişen dünyayla birlikte dönüşmekte olduğunu, bu nedenle yeni eleştirel perspektiflerle yeniden düşünülmesi gerektiğini vurgulamıştır. Sempozyum, yalnızca Türkiye’de festival çalışmalarına yönelik artan akademik ilgiyi yansıtmakla kalmamış; aynı zamanda çağdaş sinema seyirciliğinin ideolojik, mekânsal ve deneyimsel boyutlarını hesaba katan disiplinlerarası ve eleştirel yaklaşımların gerekliliğine de dikkat çekmiştir.

This paper offers a critical evaluation of the “4th Film Festival Symposium,” held on May 27–28, 2025, as part of the 22nd Eskişehir International Film Festival. Centered on the theme of “audiences of film festivals,” the symposium brought together scholars, industry professionals, and students to explore the evolving dynamics of film festivals. Over the course of two days, the program featured twenty-four paper presentations, two keynote speeches, two panel sessions, and a roundtable discussion. The presentations, addressing topics such as film festivals and industry dynamics, digitalization, shifting audience profiles, thematic film festivals and representation, national festivals, changes in sectoral dynamics, the role of festivals in shaping national and individual memory, and the rise of educational strategies and curatorial ideologies, collectively emphasized that film festivals are undergoing transformation in tandem with a changing world, and must therefore be reconsidered through new critical perspectives. The symposium not only reflected the increasing academic interest in festival studies in Türkiye but also underscored the need for interdisciplinary, critical approaches that account for ideological, spatial, and experiential dimensions of contemporary film spectatorship.
4th Film Festivals Symposium: In Pursuit of the Audiences of Film Festivals
Keywords: Cinema Studies (Other); Sinema (Diğer)